Key concepts in sport psychology - Kremer, John, 1956- (Los Angeles, Calif. : SAGE, 2012)
Concise and lively student introduction to sport psychology from a team of experienced teachers and researchers.
1. Introducing sport psychology : The history of sport psychology ; Practising sport psychology ; Ethical issues ; Organisations, sources and resources -- 2. Anxiety and stress : Anxiety and arousal ; Measuring stress and anxiety ; Pre-performance routines ; Choking under pressure ; Coping strategies -- 3. Motivation and commitment : Sport participation motives ; Burnout and dropout ; Goal setting ; Fear of failure and need to achieve ; Self-determination theory ; Achievement goal theory ; Self-efficacy and perceived competence -- 4. Cognitive processes in sport : Mental imagery ; Mental practice ; Attention and concentration ; Positive self-talk and thought control ; Mental toughness -- 5. Social psychology of sport : Team cohesion ; Team building ; Causal attribution ; Social facilitation and social loafing ; Leadership and effective coaching ; Home advantage ; Aggression ; Fans and spectators -- 6. Motor skills : Motor development ; Expertise ; Decision-making ; Practising motor skills ; Analysis and measurement of motor performance -- 7. Sport and well-being : Gender issues ; Overtraining and exercise addiction ; Injury and retirement.
Includes bibliographical references and index.
Keywords: Sports -- Psychological aspects; Sports -- Psychological aspects